Low‐grade spindle cell proliferation in clear cell renal cell carcinoma is unlikely to be an initial step in sarcomatoid differentiation. Issue 5 (31st January 2018) - Tanas Isikci, Ozlem; He, Huying; Grossmann, Petr; Alaghehbandan, Reza; Ulamec, Monika; Michalova, Kvetoslava; Pivovarcikova, Kristyna; Montiel, Delia Perez; Ondic, Ondrej; Daum, Ondrej; Prochazkova, Kristyna; Hora, Milan; et al.
Abstract : Aims: Spindle cell proliferation within clear cell renal cell carcinoma (ccRCC) is usually considered as a sarcomatoid differentiation. Low‐grade spindle cell proliferation (LG‐SCP) in ccRCC was first described in 2001. This phenomenon is not common and can pose diagnostic challenges, particularly in core biopsies. The aim of this study was to describe morphological, immunohistochemical and molecular characteristics of ccRCCs with LG‐SCP. Methods and results: Eleven cases of ccRCC with LG‐SCP were retrieved from approximately 21 000 renal tumours in our registry. Ten cases of conventional ccRCC and 10 cases of typical sarcomatoid ccRCC were included as control groups. Morphological and immunohistochemical characteristics of epithelial–mesenchymal transition (EMT) were analysed. Von Hippel–Lindau syndrome gene abnormalities were also analysed using molecular genetics. Among ccRCC with LG‐SCP cases, there were five males and five females (clinical information was not available in one case) with a median age of 67 years (mean: 68.5, range: 60–81 years). Average tumour size was 7.1 cm (median:7.5, range:1.7–12 cm). Follow‐up data were available in nine cases (mean: 44.78 months), with no aggressive behaviour seen. On average, LG‐SCP areas constituted 5–80% of tumour volume (mean: 32.3%). Necrotic/regressed areas were seen in all cases ranging from 5% to 30%. LG‐SCP was clearly epithelial, with no mitoses or any evidence of mesenchymal differentiation. Immunohistochemical profile of LG‐SCP was consistent with 'conventional' ccRCC. Compared with sarcomatoid ccRCC, some EMT markers showed alteration in LG‐SCP, including lower expression of N‐cadherin and Zeb1 as well as higher expression of E‐cadherin. However, there were no significant differences in EMT markers between LG‐SCP and conventional ccRCC. Abnormalities in VHL (mutations, LOH3p) were found in six of 11 cases. Conclusions: Our findings showed that LG‐SCP in ccRCC have comparable immunohistochemical and molecular characteristics to those seen in 'conventional' ccRCC. Further, immunohistochemical analysis of EMT markers showed that LG‐SCP did not differ from 'conventional' ccRCC. We believe that LG‐SCP is a part of morphological heterogeneity in ccRCCs and that they may not represent an initial stage of sarcomatoid differentiation. This is supported further by the fact that ccRCC with LG‐SCP did not display more aggressive behaviour than 'conventional' ccRCC.